Anthracene and pyrene photolysis kinetics in aqueous, organic, and mixed aqueous-organic phases. (March 2016) - Grossman, Jarod N.; Stern, Adam P.; Kirich, Makena L.; Kahan, Tara F.
Abstract: Condensed phases in the atmosphere, such as cloud droplets and aerosols, often contain both water and organic matter (OM). Reactivity can differ significantly between aqueous and organic phases. We have measured photolysis kinetics of the polycyclic aromatic hydrocarbons (PAHs) anthracene and pyrene in several organic solvents and in water, as well as in miscible and phase-separated aqueous-organic mixtures at atmospherically-relevant wavelengths. Photolysis rate constants generally increased with increasing solvent polarity; photolysis of both PAHs was more than ten times faster in water than in octanol. Local polarity had a much greater effect on PAH photolysis kinetics than changes in PAH absorptivity or singlet oxygen concentrations. Photolysis kinetics in homogeneous aqueous-organic mixtures varied monotonically with2 OM volume fraction. Kinetics in immiscible (phase-separated) solutions were more complex, with different dependences on OM content observed in stagnant and turbulent solutions. Our results suggest that OM could greatly affect the photochemical lifetimes of PAHs in atmospheric condensed phases such as aerosols, even if the OM does not itself absorb photons. Graphical abstract: Highlights: We have investigated the effects of organic matter on PAH photolysis kinetics. PAH photolysis kinetics in aqueous and organic phases depend primarily on polarity. Kinetics in homogeneous aerosols can be predicted by organic and aqueous fractions. Kinetics in phase-separated aqueous-organic aerosols are complex. Our results will enable more accurate predictions of PAH photolysis kinetics.